(untitled) (Fiep Bulletin - online, 2014)
It has as objective to build a theoretical-methodological approach leaving of the experiences accomplished in the daily school in a Municipal Center of Infantile Education in the Municipal City Hall of Vitória, with intention of indicating concrete possibilities of actions practices-theoretical-practices. The project/research was woven in the concrete of the school spaces/times in answers to the signs that the daily action offered. Like this, it broke of the teachers’know and of the work and collective reflections, valuing the spaces of changes among the professionals, in order to entangle significant learning for the children, inside of a context, in agreement with the projects of work delineated by CMEI "Criança Cidadã". It used, among other instruments for collection of data: filming, pictures, field diary, the children’s productions and questionnaire. The discoveries of the research evidenced a concrete possibility of pedagogic action permeated by the Pedagogy of Projects, in which, it is possible to articulate, in complex way, the different teachers’do and know. In that case, it was possible to work with the component of the curriculum of the Physical education in the Infantile Education in a collective way and integrated into the other professionals and the several knowledge areas without, however, to promote a specialization to discipline.